(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
Social awareness is the most important factor in educational achievement. Social awareness is not formed suddenly, but requires regular practice. SMA Negeri 1 Padang shapes outstanding students through various positive practices. One interesting character-building practice at SMA Negeri 1 Padang is the practice of infaq. This study aims to investigate the implementation process, impacts, as well as supporting and hindering factors of the Friday charity activity in shaping students’ social responsibility character at SMA Negeri 1 Padang. The study employs a qualitative method with a case study approach. Informants included the school principal, vice principal for student affairs, charity coordinator, PAI teacher coordinator, and six students from various grades. Data collection techniques used were observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was obtained through triangulation of techniques and sources. The results of the study indicate that the implementation of the Friday charity activity is effective and contributes to the development of social responsibility among students at SMA Negeri 1 Padang. The supporting factors for this activity include: the students’ willingness, support from the principal, teachers, and parents. Meanwhile, the inhibiting factors include: the lack of awareness among some students and differences in economic backgrounds.